(3GdeSFhdjI GdOhdjI dESQGFjd cSdWI GMJdGd ai GdVaI GdZQHjI (B: s (3JWHjb Ydi MGdI GdeSJhWfGJ (B/ s - (3LeGd YHOGdQMje eMeO eJhdis; (3eMeO SGeM YeQh s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3JTcd GdeeGQSGJ GdGSQGFjdjI ai GdGQGVi GdadSWjfjI GdeMJdI(B: (3h eMGhdGJgG dJghjO GdbOS(B: (3GfJgGcG NWjQG dbhGYO h GMcGe GdbGfhf GdOhdi h bQGQGJ efXeI GdGee GdeJMOI(B: (3h dPdc agi JSYi dEjLGO GSGfjO bGfhfjI h JaSjQGJ GMGOjI GdLGfH dbhGYO h GMcGe GdbGfhf GdOhdi h GdTQYjI GdOhdjI ci Jfai Yf faSgG UaI GdGfJgGc(B: (3hiJDSS bGfhfjG deeGQSGJgG(B: (3GedG ai JLfH GdGfJbGOGJ GdJj JhLg dgG ef bHd GdeLJeY GdOhdi(B. (3Gf GdMaGX Ydi GdMbhb GdadSWjfjI jSJdRe JafjO GdOYGhi GdGSQGFjdjI h GKHGJ VYagG h CfgG dG Jbhe Ydi SfO UMjM ef GdbGfhf(B: (3h ai faS GdhbJ GdJCcjO Ydi GfWHGb GMcGe h bhGYO GdGJaGbjGJ GdOhdjI GdJi JMce GdGMJdGd GdMQHi cGJaGbjI dGgGj dYGe (B1907: (3h GJaGbjI Lfja GdQGHYI dYGe (B1949. (3dbO JYOOJ GdeMGhdGJ GdGSQGFjdjI GdQGejI GVaGA GdTQYjI Ydi GMJdGdgG ddCQGVj GdadSWjfjI(B: (3h GbGeI GdeSJhWfGJ YdjgG(B: (3dWeS ghjJgG HMjK JHJdYgG h JVegG dCQGVjgG(B: (3h gh eG jSJdRe JMdjd Jdc GdeMGhdGJ ef efXhQ GdbGfhf GdOhdi(B: (3h GdYed Ydi JYRjR Gdehba GdadSWjfj h OYeg ddeWGdH GdTQYjI ddTYH GdadSWjfi ai GbGeI OhdJg GdeSJbdI h YGUeJgG GdbOSs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhfi GdOhdi, (B2018s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B170-184s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOhdjs; (3ESQGFjds; (3GdCQGVi GdadSWjfjI GdeMJdIs; (3SdWI GdGMJdGds; (3GdVaI GdZQHjI s; (3GdCQGVj GdadSWjfjIs; (3JbQjQ dLfI djajs; (3Mbhb GdTYH GdadSWjfj GdEbdjejI s; (3GdeSJhWfGJs; (3Mbhb GdTYH GdadSWjfj GdEbdjejI s; (3EYdGf GdOhdI GdadSWjfjI s; (3bQGQ eLdS GdCef s; (3GdGMJdGd GdMQHj s; (3GdGMJdGd GdESQGFjdj ddCQGVj GdadSWjfjIs; (3GJaGbjI Lfja GdQGHYI s; (3GdGSJjWGf aj GdbOS s; (3GfJgGcGJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs